Reproductive Biology Of Motan Fish (Thynnichthys Thynnoides) From Teluk Petai Lake, Buluh Nipis Village, Siak Hulu District, Kampar Regency, Riau Province. - Friska Girsang; Ridwan Manda Putra; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Motan fish (Thynnichthysthynnoides) is one of the fish most found in the lake of Petai. This research was conducted in March until May 2019. Samples were captured using fishing rods and sempirai fishing gear. Sampling is done 5 times in 3 months. The reproductive biology aspects measured were sexual characteristics, sex ratio, gonadal maturity level, gonadal maturity index, fecundity, and egg diameter. The sample is 109 tails (72 males and 37 females). The comparison between male and female is 2: 1. In this study, there were more male fish. The level of gonad maturity found in male and female fish TKG I-V.Gonad maturity index 0.10 - 19.08%, fecundity of 5526-9204 grains / fish and egg diameter of 0.22-025 mm. Keyword: Sex ratio, gonadal maturity level, gonadal maturity index, fecundity